2013
DOI: 10.3748/wjg.v19.i4.511
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound evaluation in the surgical treatment of duodenal and peri-ampullary adenomas

Abstract: EUS accurately predicts the depth of mucosal invasion in suspected benign ampullary and duodenal adenomas. These patients can safely undergo endoscopic or local resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In previous series, EUS understaged invasion of the duodenal muscularis propria, ranging from 8% to 15%. 5,10 Our observations suggest that EUS is more likely to understage ampullary lesions, perhaps due to missing focal invasion of the muscularis propria that is only identified by histopathological analysis of the resected specimen.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In previous series, EUS understaged invasion of the duodenal muscularis propria, ranging from 8% to 15%. 5,10 Our observations suggest that EUS is more likely to understage ampullary lesions, perhaps due to missing focal invasion of the muscularis propria that is only identified by histopathological analysis of the resected specimen.…”
Section: Discussionmentioning
confidence: 80%
“…Although several studies showed the reliability of EUS for T staging of ampullary neoplasms, these were limited by small sample size, heterogeneity of study design (combining both duodenal and ampullary lesions), or limited comparative analysis of intraductal extension with ERCP and surgical pathology. 5,8,10 …”
mentioning
confidence: 99%
“…EUS is a useful adjunct to ERCP to assess for infiltration of the periampullary wall layers and pancreatobiliary ducts but it does not have to be universally incorporated into the diagnostic evaluation of an ampullary adenoma (27,(32)(33)(34)(35)(36)(37)(38)(39). The precise role of EUS in the management of ampullary adenomas is unclear.…”
Section: Endoscopic Ultrasound (Eus)mentioning
confidence: 99%
“…EUS, in conjunction with ERCP, allows to assess for infiltration of the periampullary wall layers and pancrea tobiliary ducts but, it does not have to be universally incorpored into the diagnostic evaluation of an ampullary adenoma [45,[50][51][52][53][54][55][56][57] . The use of EUS in the assessment of AA is undefined.…”
Section: Eusmentioning
confidence: 99%